Digitising Scotland: From the North-East to the South-West - Bold, Valentina (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2001)
This article reflects on the editorial experience of collection and compilation in the generation of a CD-ROM about the traditional culture of Northern Scotland: Northem Folk (Aberdeen: The Elphinstone Institute, 1999), coedited by Valentina Bold and Tom McKean, under the general editorship of James Porter. As well as outlining the collaborative nature of the project (in terms of funding, archivai sources and specially-conducted interviews), it surveys the contents of Northern Folk, highlighting the advantages, and pitfalls, in multi-media publication. The writer reflects, too, on her current project: a companion volume exploring the traditional culture of Southern Scotland. Sharing her experience of such a project, Valentina Bold can make recommendations for the publication of future CD-ROMs dealing with ethnological material.